A Rapid and Automated Sample-to-Result Candida auris Real-Time PCR Assay for High-Throughput Testing of Surveillance Samples with the BD Max Open System - Leach, L. (J Clin Microbiol, 2019)
The multidrug-resistant yeast pathogen Candida auris continues to cause outbreaks and clusters of clinical cases worldwide. Previously, we developed a real-time PCR assay for the detection of C. auris from surveillance samples (L. Leach, Y. Zhu, and S. Chaturvedi, J Clin Microbiol 56:e01223-17, 2018, https://doi.org/10.1128/JCM.01223-17). The assay played a crucial role in the ongoing investigations of the C. auris outbreak in New York City. To ease the implementation of the assay in other laboratories, we developed an automated sample-to-result real-time C. auris PCR assay using the BD Max open system. We optimized sample extraction at three different temperatures and four incubation periods. Sensitivity was determined using eight pools of patient samples, and specificity was calculated using four clades of C. auris and closely and distantly related yeasts. Three independent extractions and testing of two patient sample pools in quadruplicate yielded assay precision. BD Max optimum assay conditions were as follows: DNA extraction at 75°C for 20 min and the use of PerfeCTa multiplex quantitative PCR (qPCR) ToughMix. The limit of detection (LOD) of the assay was one C. auris CFU/PCR. We detected all four clades of C. auris without cross-reactivity to other yeasts. Of the 110 patient surveillance samples tested, 50 were positive for C. auris using the BD Max system with 96% clinical sensitivity and 94% accuracy compared to the results of the manual assay. The BD Max assay allows high-throughput C. auris screening of 180 surveillance samples in a 12-h workday.